Traitor in Williamsburg : a Felicity mystery - Jones, Elizabeth McDavid, 1958-; Tibbles, Jean-Paul (Middleton, WI : American Girl, 2008)
Felicity, a young girl in colonial Williamsburg, decides to find out who is trying to cause trouble when an anonymous person begins falsely accusing people of helping the British--including her father.
"American Girl."
"American Girl mysteries"--Prelim. p.
5.2
3-6
Keywords: Virginia -- History -- Colonial period, ca. 1600-1775 -- Juvenile fiction; United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile fiction; Treason -- Juvenile fiction; Virginia -- History -- Colonial period, ca. 1600-1775 -- Fiction; United States -- History -- Colonial period, ca. 1600-1775 -- Fiction; Treason -- Fiction; Mystery and detective stories; Historical fiction; Virginia -- History -- Fiction; United States -- History -- 1600-1775, Colonial period -- Fiction; Treason -- Fiction; Mystery fiction; Historical fiction; Mystery fiction; Historical fiction